Evaluation of the safety and protection efficacy of an attenuated genotype vii newcastle disease virus strain as a candidate vaccine. (February 2020) - Xu, Xiaohong; Li, Jindou; Ding, Jiaxin; Yang, Mingxi; Xue, Cong; Wang, Jianzhong; Cong, Yanlong; Yin, Renfu; Qian, Jing; Jin, Ningyi; Ding, Zhuang
Abstract: Newcastle disease (ND) is a serious avian infectious disease, causing severe economic loss worldwide. Its prevention depends on comprehensive vaccination scheme against Newcastle disease virus (NDV). However, current vaccine strains are of different genotypes with prevalent circulating strains (genotype VII), with significant genetic distance. Our team previously generated a genotype matched attenuated NDV strain (rmNA-1). In this study, its safety and immunization efficacy were evaluated. Its lentogenic characteristic was stable for 25 generations in embryonated chicken eggs and for six generations in SPF chickens. Overdosed administration did not cause any clinical signs or pathogenic changes in chickens. As to its immunization effect, rmNA-1 stimulated a comparable serum NDV specific antibody level to a LaSota (genotype II) strain based commercial vaccine, and provided full protection against virulent genotype VII strain challenge, with significantly reduced virus shedding period. Highlights: Safety and efficacy of an attenuated genotype VII NDV vaccine strain was evaluated. It exhibited stable lentogenic characteristic in embryonated eggs and chickens. Provided full protection against virulent NDV attack with reduced virus shedding.